Criação, validação e confiabilidade de um equipamento de simulação de ataque no voleibol de praia - Silva, Leopoldo Sindice da (2018)
The search for improvements in the training process has been widespread for decades in sports. In this continuous performance improvement, the development of new validated instruments, with the purpose of evaluating performance, becomes a growing demand. Thus, the aim of this study was to create and validate an attack simulation equipment on beach volleyball. Therefore, the descriptive and methodological procedure was used through content validity and reliability. The sample consisted of 37 subjects with expertise in beach volleyball, with 5 expert judges (researcher, teachers, Olympic champion coach and Brazilian champion athlete), 30 experts (athletes and coaches with national and international titles or participation in Olympic Games) and 2 world champions school athlete. The results obtained indicate that all items of the instrument presented a satisfactory CVC score> 0.8. The evaluation of the instrument in its entirety, reached an excellent classification, with coefficients of 0.91 for language clarity and 0.94 for practical relevance. Regarding applicability, the simulated performance of the shot attack technique by the equipment achieved a 90% positive evaluation by the notorious group of experts. The reliability of the test-retest equipment, with significance level adopted at 5%, showed a strong and significant correlation with consistent ICC values for velocity (0.958, p <0.01) and horizontal distance (0.969; p <0.01). Considering the importance of the path traveled by the ball during the simulations, we sought to deepen the analysis of the variable vertical distance, verifying the relation between the differences and the means of the test-retest, and the low values of CV = 3.9 indicate the homogeneity of the measurements, confirming the constancy of the repetitions. It is concluded that the attack simulator is a valid equipment and presents reliability to simulate the shot type attack in beach volleyball and can be used in the evaluation of the performance for diverse purposes.